Circulating red cell-derived microparticles in human malaria. - Nantakomol, D; Dondorp, A; Krudsood, S; Udomsangpetch, R; Pattanapanyasat, K; Combes, V; Grau, G; White, N; Viriyavejakul, P; Day, N; Chotivanich, K (2011)
In patients with falciparum malaria, plasma concentrations of cell-derived microparticles correlate with disease severity. Using flow cytometry, we quantified red blood cell-derived microparticles (RMPs) in patients with malaria and identified the source and the factors associated with production. RMP concentrations were increased in patients with Plasmodium falciparum (n = 29; median, 457 RMPs/μL [range, 13-4,342 RMPs/μL]), Plasmodium vivax (n = 5; median, 409 RMPs/μL [range, 281-503/μL]), and Plasmodium malariae (n = 2; median, 163 RMPs/μL [range, 127-200 RMPs/μL]) compared with those in healthy subjects (n = 11; median, 8 RMPs/μL [range, 3-166 RMPs/μL]; P = .01). RMP concentrations were highest in patients with severe falciparum malaria (P = .01). Parasitized red cells produced >10 times more RMPs than did unparasitized cells, but the overall majority of RMPs still derived from uninfected red blood cells (URBCs). In cultures, RMP production increased as the parasites matured. Hemin and parasite products induced RMP production in URBCs, which was inhibited by N-acetylcysteine, suggesting heme-mediated oxidative stress as a pathway for the generation of RMPs.